Knowledge, Practices and Self - Reported Symptoms of Pesticides Use among Vegetable Farmers: A Cross Sectional Study in the Offinso North District - Dzobo, A. (University of Ghana, 2016)
Background: The effect of pesticide on human health and the environment is a major global public health issue. Knowledge of farmers on pesticide use and practices may contribute significantly to the burden of pesticide in human population and the environment. Objectives: This study assesses knowledge, work practices and self-reported symptoms associated with pesticide use among vegetable farmers in the Offinso North District of the Ashanti region. Methodology: The study was derived from the Offinso North district Farm Health study (ONFAHS). ONFAHS is a cross-sectional design involving 300 households in the Offinso-North district of the Ashanti region. Three hundred and ten (310) farmers who met the eligibility criteria formed the study population. Farmers were interviewed with a structured questionnaire. Results: Most farmers (88.9%) had a good knowledge on the effects of pesticides on human health and the environment. But majority adopted either poor hygienic practices (64.5%) or bad protection and safety practices (92.3%) on the job. General body weakness (89.2%) and chronic cough were common among the farmers but very few also complained of wheezing (15.4%), shortness of breath (11.2%), sexual weakness (24.5%) and depression (14.3%). Poor knowledge was associated with both respiratory and non-respiratory symptoms. Poor hygienic practices was also associated with chronic cough, breathlessness, general body weakness and depression. Protection and safety practices was associated with chronic cough, wheezing but not with non-respiratory symptoms. Conclusion This study suggests that farmers have good knowledge of the effect of pesticides on human health and the environment, but this did not translate into good work practices. General body pain was common among the farmers. Poor knowledge was associated with self-reported symptoms. However, poor work practices were associated with chronic cough and shortness of breath,
Thesis(MSc)-University of Ghana, 2016
Keywords: Vegetable Farmers; Pesticides Use; Offinso North District